Hydroxysafflor Yellow A and Anhydrosafflor Yellow B Protect Against Cerebral Ischemia/Reperfusion Injury by Attenuating Oxidative Stress and Apoptosis via the Silent Information Regulator 1 Signaling Pathway - Fangma, Yijia; Zhou, Huifen; Shao, Chongyu; Yu, Li; Yang, Jiehong; Wan, Haitong; He, Yu (Frontiers in Pharmacology, 2021)
Hydroxysafflor yellow A (HSYA) and anhydrosafflor yellow B (AHSYB) are the main water-soluble compounds in Carthamus tinctorius L. However, the studies of AHSYB on cerebral I/R injury and the therapeutic effect of HSYA by regulating SIRT1 pathway remains obscure. In this study, we investigated whether the neuroprotective effects of HSYA and AHSYB on oxygen-glucose deprivation/reoxygenation (OGD/R) in primary culture hippocampal cells and middle cerebral artery occlusion (MCAO) model in rats are associated with the regulation of SIRT1 pathway. In vitro, HSYA and AHSYB increased cell viability, depressed oxidation properties, reduced neuronal cell apoptosis. In vivo results showed that HSYA and AHSYB effectively reduced infarct volume, improved neurological function, suppressed apoptosis, and decreased oxidative stress reaction. Besides, RT-PCR and western blot showed that HSYA and AHSYB increased the mRNA and protein expressions of the main factors in SIRT1 pathway including SIRT1, FOXO1, and PGC1α, decreased the expression of Bax and increased the expression of Bcl-2. The results in immunohistochemistry also showed that the expressions of SIRT1, FOXO1, and PGC1α were increased after treatment with HSYA and AHSYB. Furthermore, the neuroprotective effects of HSYA and AHSYB were abolished by EX527 (SIRT1-specific inhibitor).These results indicated HSYA and AHSYB should be developed into the potential drugs in cerebral I/R injury via the SIRT1 pathway. Although HSYA and AHSYB have different chemical structures, both of them exert similar neuroprotection against I/R injury in vitro and in vivo, which means that AHSYB is also a not negligible component in safflower.